Peningkatan Mutu Organoleptik dan Tekstur Daging Tiruan Berbasis Kedelai dan Glukomanan untuk Intervensi Obesitas Menggunakan Jamur dan Minyak Nabati: Organoleptic and Textural Quality Improvement of Soybean and Glucomannan-Based Meat Analogs for Obesity Intervention Using Mushrooms and Vegetable Oil - Purnawijayanti, Hiasinta Anatasia; Pujiastuti, Veronica Ima; Wijayanti, M.I. Ekatrina (Amerta Nutrition, 2025)
Background: Plant-based meat analogs can be an alternative food for obesity intervention because their composition can be engineered according to criteria. The similarity of fiber structure to meat muscle, texture, sensory properties, and nutritional value determines consumer acceptance. Mushrooms have low-fat, high-quality protein, fiber, and nutraceuticals, so they have the potential for meat analogs formulation. Mushrooms also have a fibrous structure that can imitate meat texture and have a savory umami taste. Adding vegetable oil to the meat analogs formula has been shown to maintain its physicochemical properties and shelf life. Objectives: Improving organoleptic and texture quality of soy and glucomannan-based meat analog for obesity intervention. Methods: A completely randomized experimental design study was conducted with one control and four treatments. Data collected include texture profile, water-oil holding capacity, browning index, organoleptic, and satiety index test. Data were analyzed by Analysis of Variance followed by Duncan Multiple Range Test. Results: The use of mushrooms and vegetable oil in the formula affects (p-value<0.05) the aroma, water-oil holding capacity, and texture parameters of hardness bite, gumminess, and chewiness but does not affect (p-value>0.05) the appearance, taste, texture, aftertaste, liking, browning index, and texture parameters of cohesiveness, resilience, and springiness. Enoki mushrooms and corn oil tend to improve the organoleptic quality of meat analogs. The satiety index of meat analog with the addition of enoki mushrooms and corn oil is 110.4%. Conclusions: Mushrooms and vegetable oils can be used in meat analog formulations to improve their organoleptic and textural qualities.